Entrepreneurial Ecosystems: Drivers, Challenges and Success of Territories - Elisa Thomas; Bruno A. Bittencourt; Olivier Coussi; Kadígia Faccin (De Gruyter, 2024)
Delve into an exploration of dynamic entrepreneurial ecosystems in lesser-known regions around the world. Anchored in robust theoretical frameworks, this work unveils the intricate interplay of policy, culture, and innovation shaping these ecosystems. Ideal for academics, policymakers, and entrepreneurs, it offers a rich blend of practical strategies and academic insights to enhance your own research or practice.
Keywords: 300; Regional development; Entrepreneurial ecosystems; Innovation ecosystems; Public policies; Emerging economies; Entrepreneurial universities